Balancing Antioxidant, Hypolipidemic and Anti-inflammatory Activity in a Single Agent: The Example of 2-Hydroxy-2-Substituted Morpholine, 1,4-Benzoxazine and 1,4-Benzothiazine Derivatives as a Rational Therapeutic Approach against Atherosclerosis - N. Matralis, Alexios; Bavavea, Eugenia-Ismini; Incerpi, Sandra; Z. Pedersen, Jens; P. Kourounakis, Angeliki (Current Medicinal Chemistry, 2017)
In line with our previous studies, novel morpholine and benzoxa(or thia)zine lead compounds have been developed through a rational design that modulate a multiplicity of targets against atherosclerosis. We have evaluated the most promising compounds for their efficiency to a) intercept and scavenge free radicals, b) inhibit the metal ion (Cu2+)-induced LDL oxidation c) act intracellularly as antioxidants in THP-1 monocytes from a leukemic patient and d) inhibit the pro-inflammatory enzymes cyclooxygenase-1 (COX-1) and -2 (COX-2) in vitro. Furthermore, two representative compounds were tested for their potential to decrease lipidemic parameters (TC, LDL and TG) in hyperlipidemic mice. Most derivatives indicated a remarkable antioxidant activity, while at the same time exhibited a significant in vitro anti-inflammatory activity, inhibiting COX-1 or/and COX-2 activity at 20 μ. In addition, after their long-term administration, compounds 6 and 8 afforded considerable activity in a chronic experimental animal model of hyperlipidemia (after high fat diet administration). The multifunctional pharmacological profile exhibited by the compounds of this study renders them interesting lead compounds for the development of novel agents against atherosclerosis.
Keywords: microsomes